The Impact of Climate on Holiday Destination Choice - Richard S.J. Tol; Andrea Bigano; Jacqueline M. Hamilton (Fondazione Eni Enrico Mattei (FEEM), 2005)
The holiday destination choice is analysed for tourists from 45 countries, representing all continents and all climates. Tourists are deterred by distance, political instability and poverty, and attracted to coasts. Tourists prefer countries with a sunny yet mild climate, shun climes that are too hot or too cold. A countrys tourists aversion for poverty and distance can be predicted by that countrys average per capita income. The preferred holiday climate is the same for all tourists, independent of the home climate. However, tourists from hotter climates have more pronounced preferences.
Keywords: L83; Q25; 330; Climate change; Impacts; Adaptation; Acclimatisation; Domestic tourism; International tourism; Tourismus; Internationaler Tourismus; Klimaveränderung; Klima; Welt